METODE DAN TEKNIK PENERJEMAHAN KARYA SASTRA - Yuliani Rahmah (KIRYOKU, 2018)
(Title: Methods and Techniques of Translating Literary Works) With the mass media globalization today, a literary works can be translated into many different languages. This situation makes the translation literature become one of the prose that is in great demand by literary learners. A good translation literature cannot be separated from the translation system that can convey the contents of a literary work in the target language as well as in the original language. To get a good translation process, an interpreter (specially the beginner) must know the right way to transfer the original language into the target language. Difficulty translating literary works can be solved by the knowledge of translation. This article will explain about that knowledge which includes types, techniques and methods of translation. The purpose of this presentation is to provide some information for the Japanese language learners, especially those who learns the Japanese literature. Using the literature study method, it can be seen that there are three types of translation which include intralingual translation, interlingual translation and intersemiotic translation. The three types of translation can be translated by choosing the right method and technique from eight translation methods and nine translation techniques. By choosing the right method and technique, a translation literature is not only translated into the language system, but can also be further translated along with the sign and cultural meaning implied by that literary work.